This page does not represent the most current semester of this course; it is present merely as an archive.

# 1 Equivalences

Two expressions are equivalent if they have the same truth valuation regardless of

## 1.1 Simplifications

Simplifications have the property that they make expressions smaller, with fewer operators and propositions. They are equivalences so they also work backwards (i.e. making expressions larger), a process sometimes called introduction, as in we can introduce a double negation

The first five are big and worth memorizing

long simplified Name of rule
\lnot \lnot P P double negation
P \land \bot \bot
P \land \top P
P \lor \bot P
P \lor \top \top

and the rest are either less commonly useful or can be derived from the five above rules

simplified \rightarrow \leftrightarrow \oplus \land \lor
P \top \rightarrow P
\lnot P \rightarrow P
\top \leftrightarrow P \bot \oplus P \top \land P
P \land P
\bot \lor P
P \lor P
\lnot P P \rightarrow \bot
P \rightarrow \lnot P
\bot \leftrightarrow P \top \oplus P
\top \bot \rightarrow P
P \rightarrow \top
P \rightarrow P
P \leftrightarrow P P \oplus \lnot P \top \lor P
P \lor \lnot P
\bot P \leftrightarrow \lnot P P \oplus P \bot \land P
P \land \lnot P

## 1.2 Other equivalences

The following operators are both associative (you can add and remove parentheses around them) and commutative (you can swap their operands’ position): \land, \lor, \oplus

The following operator is commutative but not associative: \leftrightarrow

Of the other rules here, the first several are worth memorizing

form 1 form 2 Name of rule
A \rightarrow B \lnot A \lor B
A \land (B \lor C) (A \land B) \lor (A \land C) Distributive law
A \lor (B \land C) (A \lor B) \land (A \lor C) Distributive law
\lnot (A \land B) (\lnot A) \lor (\lnot B) De Morgan’s law
\lnot (A \lor B) (\lnot A) \land (\lnot B) De Morgan’s law
(A \leftrightarrow B) (A \rightarrow B) \land (B \rightarrow A)
(A \oplus B) (A \lor B) \land \lnot (A \land B)

and the rest are either less commonly useful or can be derived easily from other worth-memorizing rules

form 1 form 2 Name of rule
A \oplus B \lnot (A \leftrightarrow B)
A \leftrightarrow B \lnot (A \oplus B) xnor
P \rightarrow (A \lor Q) (P \land \lnot A) \rightarrow Q

# 2 Entailments

## 2.1 Logical entailment

Given Entails Name
\bot {x}
{\top}
{A \lor \lnot A} excluded middle
A \land B {A}
A and B {A \land B}
A {A \lor B}
A \lor B and \lnot B {A} disjuctive syllogism
A \rightarrow B and B \rightarrow C {A \rightarrow C} hypothetical syllogism; transitivity of implication
A \rightarrow B and A {B} modus ponens
A \rightarrow B and \lnot B {\lnot A} modus tolens
A \leftrightarrow B {A \rightarrow B}
{A \rightarrow C}, {B \rightarrow B}, and {A \lor B} {C}
{A \rightarrow B}, {C \rightarrow D}, and {A \lor C} {B \lor D}
A \rightarrow B {A \rightarrow (A \land B)}
\lnot(A \land B), A {\lnot B}

## 2.2 Assume-and-prove entailment

A proof that assumes A and derives B entails that A \rightarrow B. This is commonly used in the inductive step of a proof by induction.

A proof that assumes A and derives \bot entails that \lnot A. This is called proof by contradiction or indirect proof.